2018
DOI: 10.1029/2017jd027818
|View full text |Cite
|
Sign up to set email alerts
|

Brown and Black Carbon Emitted by a Marine Engine Operated on Heavy Fuel Oil and Distillate Fuels: Optical Properties, Size Distributions, and Emission Factors

Abstract: We characterized the chemical composition and optical properties of particulate matter (PM) emitted by a marine diesel engine operated on heavy fuel oil (HFO), marine gas oil (MGO), and diesel fuel (DF). For all three fuels, ∼80% of submicron PM was organic (and sulfate, for HFO at higher engine loads). Emission factors varied only slightly with engine load. Refractory black carbon (rBC) particles were not thickly coated for any fuel; rBC was therefore externally mixed from organic and sulfate PM. For MGO a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
90
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 91 publications
16
90
0
Order By: Relevance
“…In addition to the characterization of the particle optical properties detailed in the next section, a set of online and offline techniques were used for the characterization of the gaseous and particulate emissions before and after aging. The nonrefractory particle size-segregated chemical composition was measured with a high-resolution (HR) timeof-flight aerosol mass spectrometer (AMS) (DeCarlo et al, 2006). Uncertainties related to particle collection efficiency in the AMS are considered negligible for the relatively large particles sampled here, which in terms of volume are within the size range transmitted efficiently by the AMS aerodynamic lens (Liu et al, 2007).…”
Section: Smog Chamber Experimentsmentioning
confidence: 99%
“…In addition to the characterization of the particle optical properties detailed in the next section, a set of online and offline techniques were used for the characterization of the gaseous and particulate emissions before and after aging. The nonrefractory particle size-segregated chemical composition was measured with a high-resolution (HR) timeof-flight aerosol mass spectrometer (AMS) (DeCarlo et al, 2006). Uncertainties related to particle collection efficiency in the AMS are considered negligible for the relatively large particles sampled here, which in terms of volume are within the size range transmitted efficiently by the AMS aerodynamic lens (Liu et al, 2007).…”
Section: Smog Chamber Experimentsmentioning
confidence: 99%
“…Recent work has highlighted another, brown-colored form of light-absorbing, carbonaceous PM (LAC) with unknown chemical composition. 4,6 This non-BC LAC was treated in those works as "soluble brown carbon" (soluble brC) in the conventional [7][8][9] sense: a complex, liquid-like mixture of light-absorbing organic molecules that are volatilizable, miscible with non-light absorbing PM components such as organic aerosol, and soluble in common organic solvents. These properties imply a number of physical consequences, such as optical properties (and climate impacts) governed by internal mixing with non-absorbing PM, 10 and justify the use of solvent extraction as a standard technique for studying brC.…”
Section: Introductionmentioning
confidence: 99%
“…The absolute absence of the large BC particles in the older plumes might be explained by their extremely scarce number abundance, which, especially after dilution, makes their sampling probability very low. Although previous in situ observations did not report a second peak at larger D rBC (Buffaloe et al, 2014), recent laboratory tests (Corbin et al, 2018) confirmed that vessel engines running on heavy fuel oil emit large BC cores. Under such conditions, the rBC size volume distribution is bimodal, with geometric mean of the smaller and larger peak of 150 nm and 640 nm respectively.…”
Section: Ship Emissions In the Arkona Basinmentioning
confidence: 82%